Effects of sodium nitroprusside in the prevention of schizophrenia-like symptoms induced by ketamine – A translational double-blind study - Tatiana M. N. Rezende (Archives of Clinical Psychiatry)
Abstract Background: Recent evidence has shown improvements in schizophrenia symptoms after the infusion of sodium nitroprusside (SNP), a nitric oxide (NO) donor. In the rat model of schizophrenia using ketamine injection, pretreatment with SNP seems to prevent behavioral changes associated with positive symptoms for up to one week. Objective: We investigated whether SNP would have preventative effects on psychogenic symptoms induced by ketamine in healthy subjects. Methods: Healthy subjects (N = 38) were assigned to distinct groups that received SNP in different doses (0.15, 0.25, and 0.5 mcg/kg/min). First, participants received an infusion of SNP or placebo over 75 minutes. After 10 minutes, they were injected for 1 minute with a bolus of 0.26 mg/kg of ketamine and a maintenance dose was started 5 minutes later, with 0.25 mg/kg/h of ketamine for 50 minutes. Results: Ketamine-induced psychopathological alterations induced were reduced by SNP, as assessed with the Brief Psychological Rating Scale. Scores in the objective subscale of the Clinician-Administered Dissociative States Scale were also lower in SNP sessions compared to placebo. SNP had protective effects against deterioration in facial emotion and identity recognition tasks induced by ketamine. Discussion: Our findings support the view that SNP has preventative properties against psychotic manifestations.